2015
DOI: 10.1371/journal.pone.0135004
|View full text |Cite
|
Sign up to set email alerts
|

Study of Nonlinear MHD Tribological Squeeze Film at Generalized Magnetic Reynolds Numbers Using DTM

Abstract: In the current article, a combination of the differential transform method (DTM) and Padé approximation method are implemented to solve a system of nonlinear differential equations modelling the flow of a Newtonian magnetic lubricant squeeze film with magnetic induction effects incorporated. Solutions for the transformed radial and tangential momentum as well as solutions for the radial and tangential induced magnetic field conservation equations are determined. The DTM-Padé combined method is observed to demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 36 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…The hall effect, viscous dissipation and induced magnetic field are assumed to be negligible because of the magnetic Reynolds number of the flow is considered to be very small. 5. It is assumed that voltage is not applied which implies the absence of an electric field.…”
Section: Mathematical Formulation Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The hall effect, viscous dissipation and induced magnetic field are assumed to be negligible because of the magnetic Reynolds number of the flow is considered to be very small. 5. It is assumed that voltage is not applied which implies the absence of an electric field.…”
Section: Mathematical Formulation Of the Problemmentioning
confidence: 99%
“…This type of flow was analyzed by Singh et al [1], Gorla et al [2] and Kearsley et al [3]; Umavathi et al [4] studied the generalized plain heat transfer of Couette flow in a composite channel. The system of non-linear differential equations of a newtonian magnetic lubricant squeeze film flow with magnetic induction effects were solved by Rashidi et al [5] using the combination of the differential transform and Padé approximation methods. Freidoonimehra et al [6] investigated the transient magnetohydrodynamic free laminar convective flow of nano-fluid past a vertical porous and stretched surface under acceleration by considering four different types of water based nano-fluid namely, copper (Cu), copper oxide (CuO), aluminum oxide (Al 2 O 3 ), and titanium dioxide (TiO 2 ) using a fourth order Runge-Kutta method based shooting technique.…”
Section: Introductionmentioning
confidence: 99%
“…(4), one can obtain (for more details, see Refs. , Rashidi et al (2015), Rashidi and Freidoonimehr (2014)):…”
Section: Application Of Dtmmentioning
confidence: 99%
“…Further, Abbasi et al [26] developed a mathematical model of peristaltic transport of MHD fluid by considering Entropy 2016, 18, 117 3 of 16 variable viscosity. Some relevant studies to magnetic field models can be found from the list of references [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%